Pengaruh Pemanfaatan Media Pembelajaran Audiovisual Dalam Upaya Peningkatan Motivasi Belajar Dan Adversity Quotient Terhadap Prestasi Belajar Mata Pelajaran Matematika (STUDI KASUS : SMK ROSMA KARAWANG) - Rini Malfiany (LPPM STMIK Rosma, 2017)
This researsch aims to determain: 1). Effect of Learning Audiovisual media on motivation improvement efforts. 2). Influence motivation toward learning achievement. 3). Influence on learning achievement adversity quotient. The study was conducted at SMK Rosma Karawang which Class X TKJ is as experiment class, and Class X AP is as benchmark class. Experimental method is used as the research methodology, while multi stages random sampling are applied for extraction of samples, and the techniques of data collection used are value and survey. The value and survey find out the students' learning motivation and adversity quotient students. The tools tested in Class X and Class X TKJ SMK AP Rosma Karawang, using SPSS ver 16.0 for validity and reliability testing of 20 search queries. The results of reliability test indicate that the variable coefficient alpha is > 0.06 means all questions in each variable is relliable. Based on data analysis can be concluded that: 1) There was a significant effect of the use of audiovisual media on learning achievement mathematics courses with a P *** 5% significance level means rejected. 2) There is no significant effect of learning motivation on learning achievement level of significance of 5% means acceptable, but a significant level of 1% was rejected. 3) There is no significant influence of adversity quotient on learning achievement in mathematics at the 5% significance level that is acceptable. Providing feedback for teachers of SMK Rosma to use Audiovisual in learning process is one of the expectation from the results of this reseearsch. Besides, the school can pay more attention for growing up the students’ motivation as well as giving support to adversity quotient students up to the high level.